Fenomena Hijrah Pegawai Bank Pada Komunitas XBank Di Kota Makassar - Nuraeni Nuraeni; Fitri Ramdani; Trimulato Trimulato (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This study aims to describe the motivation for migrating to the Xbank community in Makassar, then describe the community's views on Islamic banks and Xbank's activities after leaving work from conventional financial institutions. The method used in this research is qualitative by conducting field research. The primary data source is direct interviews with the Xbank community in Makassar city and secondary data. The analysis technique used in this research is content-based descriptive qualitative. The results of the study found that the migration phenomenon of the Xbank community in Makassar city was more related to the views of the XBank community towards Islamic banking activities. The motivation for migrating is that they believe that conventional financial institutions contain the common element of usury. The XBank community in Makassar accepts the existence of Islamic banks but instead provides criticism if transactions are not under sharia principles. This research can be input for Islamic financial institutions in carrying out financial practices to avoid transactions Islam prohibits.